Understanding the Communicative Intentions of the Speaker and Peer’s Popularity Among Children of Primary School Age - E.I. Lebedeva (Психолого-педагогические исследования)
The aim of this study was to explore the role of the theory of mind – the ability to attribute mental states to other people in order to explain their behavior – in popularity with peers and in the social competence of children of primary school age. The participants were 92 children aged 9–12 years (M=9,97; SD=0,80; 47 girls). We used the F. Happé “Strange Stories” test, used to study children's understanding of the speaker's communicative intentions in situations of ambiguously understood social interactions, to assess theory of mind. The popularity of children in the group was studied using a sociometric method. For an external evaluation teachers assessed the social behavior of children and adolescents using a specially designed questionnaire. The results obtained testify to the relationship of children’s theory of mind with both their popularity with peers, and with their social competence as a whole. The understanding of communicative intentions in difficult social situations by children is related with both peer preference for socializing and perceived popularity among peers. An external assessment of social competence among primary school age children by teachers has shown that children who are more successful in understanding the communicative intentions of other people are rated by adults as more popular among their peers, while the less successful ones are those who more often become the object of ridicule and often fall under the negative influence of others.